Can Immunogenic Chemotherapies Relieve Cancer Cell Resistance to Immune Checkpoint Inhibitors? - Rivera Vargas, Thaiz; Apetoh, Lionel (Frontiers in Immunology, 2019)
The unprecedented clinical activity of checkpoint blockade in several types of cancers has formally demonstrated that anti-tumor immune responses are crucial in cancer therapy. Durable responses seen in patients treated with immune checkpoint inhibitors (ICI) show that they can trigger the establishment of long-lasting immunologic memory. This beneficial outcome is however achieved for a limited number of patients. In addition, late relapses are emerging suggesting the development of acquired resistances that compromise the anticancer efficacy of ICI. How can this be prevented through combination therapies? We here review the functions of immune checkpoints, the successes of ICI in treating cancer and their therapeutic limits. We discuss how conventional cancer therapies can be properly selected to set up combinatorial approaches with ICI leading to treatment improvement. We finally summarize clinical data showing the ongoing progress in cancer treatment involving ICI and chemotherapy combination strategies.